Importance of medical prevention in medicine - Asfandiyorov Javodbek Mirzaali o’g’li; Xushvaqtov Ilyos Shodiqul o’g’li; Sultonmirzayev Xikmatillo Eminjon o’g’li; Norboyev Baxrom Aliqul o’g’li; Mardonov Mirzabek Begzod o’g’li (Zien Journals, 2022)
This article discusses the history of medicine, its past and future. Medicine has set before itself today goals are widely discussed.
Keywords: theoretical activity; practical activity; integration; idealization